2014
DOI: 10.1016/j.expneurol.2013.11.023
|View full text |Cite|
|
Sign up to set email alerts
|

A tetra(ethylene glycol) derivative of benzothiazole aniline ameliorates dendritic spine density and cognitive function in a mouse model of Alzheimer's disease

Abstract: We recently reported that the tetra(ethylene glycol) derivative of benzothiazole aniline, BTA-EG4, acts as an amyloid-binding small molecule that promotes dendritic spine density and cognitive function in wild-type mice. This raised the possibility that BTA-EG4 may benefit the functional decline seen in Alzheimer’s disease (AD). In the present study, we directly tested whether BTA-EG4 improves dendritic spine density and cognitive function in a well-established mouse model of ADcarrying mutations in APP, PS1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
3
32
1
1
Order By: Relevance
“…Previous work has reported that BTA-EG 4 and BTA-EG 6 could promote spine density increases in vitro in murine primary hippocampal neurons (37) and BTA-EG 4 could promote spine density increases in vivo in the hippocampus of wt mice and a 3ϫ tg mouse model for AD (18,19). The increase in spine density in neurons by BTA-EG 4,6 correlated with an increase in expression of RasGRF1 compared with control cells (37).…”
Section: Design and Evaluation Of Benzothiazole Amphiphiles (Bams) 1-mentioning
confidence: 82%
See 3 more Smart Citations
“…Previous work has reported that BTA-EG 4 and BTA-EG 6 could promote spine density increases in vitro in murine primary hippocampal neurons (37) and BTA-EG 4 could promote spine density increases in vivo in the hippocampus of wt mice and a 3ϫ tg mouse model for AD (18,19). The increase in spine density in neurons by BTA-EG 4,6 correlated with an increase in expression of RasGRF1 compared with control cells (37).…”
Section: Design and Evaluation Of Benzothiazole Amphiphiles (Bams) 1-mentioning
confidence: 82%
“…In conclusion, we used rational design to develop a novel set of benzothiazole amphiphiles 1-3 with improved biocompatibility compared with the previously reported BTA-EG 4,6 compounds (17)(18)(19). These new compounds were capable of 1) promoting dose-dependent increases in dendritic spine density, 2) temporally and reversibly controlling elevated spine levels, and 3) protecting against A␤-induced dendritic spine loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for this observation is that catalase ameliorates Aβ toxicity via two independent ways, firstly it decreases elevated ROS levels and secondly that it acts as a scavenger of Aβ and the latter function is blocked by BTA-EG 4 [173]. However, the latest study demonstrated that BTA-EG 4 produces an age-specific improvement in synaptic density and cognitive function in an AD mouse model, when administered daily for two weeks and an associated change in dendritic spine density with increased Ras activity [174]. Additionally, polyphenol phloroglucinol ( Fig.…”
Section: Catalasementioning
confidence: 98%